KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS RUMBAI KOTA PEKANBARU DAN FAKTOR YANG BERHUBUNGAN - NURVI SUSANTI; ZULMELIZA RASYID (JURNAL PROTEKSI KESEHATAN, 2015)
Accordingon the profile of the health of Riau Provincein 2011, Case Detection Rate (CDR) is still below the national target of 70%. Whereas the achievement of these national targets are 90% out of 100%. Toddler’s pneumonia sufferers were estimated at as much as 10.940 Riau Province sufferers or 1704 invention of pneumonia cases (15.6 percent), while cases of toddler’s pneumonia who prevail in Rumbai Health Center 82.4%. Thus pneumonia is still a health problem because it can cause a rapid death if not treated promptly. This research goalsto find out the prevalence of toodler’s pneumonia incidence as well as knowing the gender relations, knowledge of mother, mother's education, mother's work status, BBLR, immunization status, exclusive breast feeding, housing density, and the role of health workers by number incidence of pneumonia in rumbai health centerpekanbaru city work area.The research is using quantitative analysis with the design case control.Population consist ofpopulationcases and population control.Sample case was 98 toddlers’ whos suffer from toddler’s pneumoniain rumbai health centerpekanbaru city work area.The sampling technique is using simple random sampling, and data anlysis are univariat, bivariat, and multivariat, with logistic regression test. The research resultsshowed that all variables (9 variables has significancy with pneumonia toddlers, which are sex OR 4,304 (CI 95 %: 2,36-7,85), education OR 4,267 (CI 95 % 2,34-7,75 ), work OR 0,516 (CI 95 % 0,28-0,92 ), knowledge OR 1,947 (CI 95 % 1,10-3,44 ), BBLROR 4,002 (CI 95 % 2,16 -7,39) , immunization status OR 20,938 (CI 95 % 9,55-45,49 , exclusive breast feeding OR 4,500 (CI 90 % 2,46-8,21 ) , housing densityOR 2,212 (CI 95 % 1,22-3,95 ) , the role of health workers OR 1,947 (CI 95 % 1,10- 3,44 ). Multivariate analysis showed variable most dominant were immunization status with p value = 0.0001 OR 95 % CI 13,582 (5,590-33,004)). Conclusions,It is necessary to spread information and sendhealth promotion team to hold health counseling to women who had pneumonia toddlers particularly on penumonia disease.